A Web-Based Remote Access Laboratory Using SCADA - Aydogmus, Zafer; Aydogmus, Omur (Ieee-Inst Electrical Electronics Engineers Inc, 2009)
The Internet provides an opportunity for students to access laboratories from outside the campus. This paper presents a Web-based remote access real-time laboratory using SCADA (supervisory control and data acquisition) control. The control of an induction motor is used as an example to demonstrate the effectiveness of this remote laboratory, using real instruments (a two-level inverter, measurement equipment, a magnetic powder brake and an ac/dc converter). A programmable logic controller (PLC) was programmed to control the operation of the system and a SCADA system was installed to monitor and control of the process. Some limitations were placed on the PLC program to protect the motor from overloading and going over maximum speed. The remote laboratory presented here offers an economical solution for multiple users in a laboratory environment. This system allows the students to access real instruments in a real laboratory via the Internet. Additionally, the suggested architecture helps improve students' skills on SCADA systems in use in industry. The Web interface was designed using Visual Studio with ASP.NET, which allows students to-access the lab and information about the experiment.
Keywords: Programmable logic controller (PLC); remote access lab; supervisory control and data acquisition (SCADA); Web-based education